Preparation method of columnar crystal yttrium oxide / magnesium oxide composite ceramic powder
Patent Information
- Application Number
- CN202411566290.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing Y2O3-MgO ceramics are difficult to form columnar crystals, and their mechanical properties are poor, which limits their application.
High-temperature ceramic melt is synthesized through ultra-high temperature combustion between magnesium powder and oxygen. After rapid cooling in the liquid phase, a micron-scale metastable supersaturated solid solution and amorphous mixture ceramic powder are formed, and columnar crystals are induced in situ during the sintering process. .
It achieves the formation of high-density columnar crystals in Y2O3-MgO ceramics, significantly improves the strength and toughness of the ceramics, and increases the fracture toughness by about 50%.
Smart Images

Figure CN119350028A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite ceramic materials, and in particular to a method for preparing columnar crystal yttrium oxide / magnesium oxide composite ceramic powder. Background Art
[0002] Y2O3-MgO nanocomposite materials have been widely studied as a representative infrared transparent ceramic due to their excellent thermal and optical properties, and have broad application prospects in the fields of infrared windows, solid-state lasers, and transparent armor. However, the mechanical properties of Y2O3-MgO nanocomposite ceramics are poor, which seriously hinders their application. Therefore, it is urgent to develop a new transparent ceramic material with high strength, broadband and high transmittance.
[0003] At present, the preparation methods of Y2O3-MgO composite ceramic powders mainly include sol-gel method, glycine-nitrate method, flame spray pyrolysis method and solid phase ball milling method. After sintering, the Y2O3-MgO composite ceramic powders prepared by these methods have equiaxed grains in the composite ceramics, and the mechanical properties of the composite ceramics are poor, which limits the application of Y2O3-MgO composite ceramics.
[0004] For most ceramics, the introduction of columnar crystals inside the ceramics will greatly improve their fracture toughness and strength. There are two main methods for introducing columnar crystals into ceramics. The first is to add a small amount of columnar crystal / whisker micron powder or nano powder into the ceramic matrix to prepare columnar crystal-containing ceramics. This method is prone to uneven distribution when the amount of columnar crystal / whisker added is small, resulting in large performance differences; when the amount added is large, the nano powder not only has problems such as easy agglomeration and easy grain growth, but also with the increase in the amount of addition, the columnar crystal / whisker plays a skeleton role, which is difficult to sinter densely, thereby greatly reducing the strengthening effect. The second method is to add an inducer to the ceramic powder, and columnar crystal ceramics can be induced in situ during the sintering process. The inducer of this method is rare earth oxide. This in-situ method increases the content of columnar crystals, thereby improving the performance of ceramics. At present, there are literature reports on the strengthening and toughening of columnar crystals in ceramics such as Al2O3-ZrO2 and SiN3, but columnar crystals have not yet been reported in Y2O3-MgO ceramics. Summary of the invention
[0005] The invention aims to solve the problem that the existing Y2O3-MgO ceramics are difficult to form columnar crystals and have poor mechanical properties, and provides a method for preparing columnar crystal yttrium oxide / magnesium oxide composite ceramic powder.
[0006] The method for preparing columnar crystal yttrium oxide / magnesium oxide composite ceramic powder of the present invention comprises the following steps:
[0007] Step 1: drying magnesium powder and a diluent; the diluent is a mixture of magnesium oxide and yttrium oxide, wherein magnesium oxide accounts for 0 to 28.19% of the total mass of the diluent;
[0008] Step 2: Evenly mix the dried magnesium powder and the diluent to obtain a mixed material; wherein the mass fraction of the magnesium powder in the mixed material is 13.45% to 24.2%, and the mass fraction of the diluent is 75.8% to 86.55%;
[0009] Step three: Load the mixed material into a high-pressure reactor, fill the high-pressure reactor with O2 or O2 mixed gas, and provide a nozzle at the lower end of the reactor, the nozzle having a nozzle diameter of 1 to 5 mm, ignite the mixed material, and perform a high-temperature combustion synthesis reaction at a reaction temperature of 3300 to 4500 K. After the reaction is completed, a high-temperature melt is formed, which is kept warm for 5 to 40 seconds, and then the nozzle is opened to spray out the high-temperature melt. After the high-temperature melt is cooled in the liquid phase, a columnar crystal yttrium oxide / magnesium oxide composite ceramic powder can be obtained; wherein the high-temperature melt spraying pressure is set to 10 to 40 MPa.
[0010] Furthermore, the columnar crystal yttrium oxide / magnesium oxide composite ceramic powder obtained in step three is sintered to obtain submicron columnar crystal yttrium oxide / magnesium oxide composite ceramic.
[0011] Furthermore, the sintering process is pressureless sintering, hot pressing sintering, spark plasma sintering or flash sintering.
[0012] Preferably, the sintering process conditions are: heating rate 5-100° C. / min, sintering temperature 1100-1500° C., and holding time 5 min-3 h.
[0013] Furthermore, the columnar crystalline yttrium oxide / magnesium oxide composite ceramic powder obtained in step 3 is first subjected to high-energy ball milling to 100-500 nm, and then sintered. The high-energy ball milling speed is 1000-2000 r / min, and the ball milling time is 6-12 hours.
[0014] Furthermore, the columnar crystal yttrium oxide / magnesium oxide composite ceramic powder obtained in step 3 is first sand-milled to 50-500 nm, and then sintered. The motor speed of the sand mill is 1500-2030 r / min, and the sand milling time is 4-10 hours.
[0015] Principle of the present invention:
[0016] The present invention obtains a high-temperature ceramic melt by ultra-high temperature combustion synthesis between magnesium powder and oxygen, and the chemical reaction that occurs is shown in formula (1). The high-temperature melt is rapidly cooled through the liquid phase to obtain a metastable supersaturated solid solution and amorphous mixture ceramic powder of micrometer level. In the combustion synthesis process, different reaction systems have different process characteristics, and a large amount of experiments and theoretical work are required for process realization, process optimization and process stability. For the Y2O3-MgO system, the melting point of the oxide is relatively high, and a very high temperature needs to be reached to completely melt the oxide. In addition, the particle size of the magnesium powder raw material is relatively large (about 44μm), and the uniformity needs to be verified after the reaction forms a high-temperature melt. In addition, due to the high activity and volatility of magnesium powder, in the high-temperature and high-pressure reaction process, the safety problem needs to be solved urgently, and a large amount of experimental exploration and theoretical analysis are required to ensure the safety and reliability of the process. After preliminary process research, the uniform mixing of the high-temperature melt can now be achieved, and the safety of the method is ensured.
[0017]
[0018] Whether the metastable supersaturated solid solution and amorphous mixture obtained by rapid cooling of high-temperature melt can induce columnar crystals is closely related to the material system and process parameters. It is still difficult to make reasonable predictions through theory at present, and experimental verification is required. After process optimization, the micron-level metastable Y2O3-MgO supersaturated solid solution and amorphous mixture ceramic powder prepared by the present invention can induce high-density columnar crystals in situ in the ceramic during the subsequent high-temperature sintering process. The formation of columnar crystals is to obtain the high-temperature stable phase m-Y2O3 of Y2O3 by combining the method of rapid cooling of the liquid phase with the high-temperature melt. During the sintering process, m-Y2O3 transforms to the low-temperature stable phase c-Y2O3 and grows along the preferred orientation direction to form high-density columnar crystals, thereby improving the strength and toughness of Y2O3-MgO composite ceramics. In addition, according to the Y2O3-MgO phase diagram, the solid solubility of the two phases is extremely low, and in the high-temperature melt state, the two can be mutually soluble, and this solid solution state is retained by rapid cooling. During the sintering process, the supersaturated solid solution undergoes dissolution and precipitation, forming small nano-scale or submicron-scale particles inside the grains. The presence of such small particles will hinder the migration of grain boundaries during grain growth, thereby controlling the grain size of Y2O3-MgO ceramics, achieving the effects of columnar crystal strengthening and fine grain strengthening, and further improving the strength of the composite ceramics.
[0019] The present invention sintered the obtained micron-level metastable Y2O3-MgO supersaturated solid solution and amorphous mixture ceramic powder, in situ induced columnar crystals during the transformation of m-Y2O3 to c-Y2O3, and the Y2O3-MgO supersaturated solid solution was desolvated and precipitated to form a nano-reinforced phase during sintering, forming a high-density and uniformly distributed columnar crystal intra-crystalline / inter-crystalline composite nanostructure, thereby obtaining a high-strength and high-toughness columnar crystal yttrium oxide / magnesium oxide composite ceramic. At present, this columnar crystal intra-crystalline / inter-crystalline composite nanostructure has not been reported in yttrium oxide / magnesium oxide composite ceramics, and is of great significance for improving the strength and toughness of yttrium oxide / magnesium oxide composite ceramics.
[0020] Beneficial effects of the present invention:
[0021] 1. The method of the present invention obtains for the first time a micron-sized metastable Y2O3-MgO supersaturated solid solution and an amorphous mixture ceramic powder, wherein the components in the powder are evenly distributed.
[0022] 2. During the sintering and densification process of the metastable Y2O3-MgO supersaturated solid solution and amorphous mixture ceramic powder prepared by the method of the present invention, m-Y2O3 transforms into a low-temperature stable phase c-Y2O3 and grows along the preferred orientation direction to form high-density columnar crystals with a submicron size, and the length of the columnar crystals can be controlled by adjusting the sintering process parameters. This structure has not been reported in Y2O3-MgO composite ceramics before.
[0023] 3. During the sintering and densification process of the metastable Y2O3-MgO supersaturated solid solution and amorphous mixture ceramic powder prepared by the method of the present invention, the Y2O3-MgO supersaturated solid solution formed by mutual dissolution at high temperature undergoes precipitation and precipitation, and small nano-reinforced phase particles are generated in situ inside. The presence of such small particles will hinder the migration of grain boundaries during grain growth, thereby controlling the grain size of the Y2O3-MgO ceramic, achieving the effect of fine grain strengthening, and further improving the strength of the composite ceramic.
[0024] 4. The ceramic powder prepared by this method can obtain columnar crystal yttrium oxide / magnesium oxide composite ceramics during the densification process. Due to the high content of columnar crystals and small grain size, the strength and toughness of the ceramics are significantly increased. When the sintering temperature is 1000-1500℃, the hardness of the yttrium oxide / magnesium oxide composite ceramics is 10-15GPa, and the fracture toughness is 3-5MPa·m 1 / 2 , compared with the existing technology, the fracture toughness is improved by about 50%.
[0025] 5. The method of the present invention can prepare a large amount of supersaturated solid solution columnar crystal powder, and the preparation cost of the powder is low, the benefit is high, and it has a very high prospect for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 XRD patterns of the columnar yttrium oxide / magnesium oxide composite ceramic powder prepared in Example 1 after heat treatment at different temperatures;
[0027] Figure 2 The cross section and element distribution of the columnar crystal yttrium oxide / magnesium oxide composite ceramic powder prepared in Example 1;
[0028] Figure 3 The microscopic morphology of the yttrium oxide / magnesium oxide composite ceramic powder prepared in Example 1 after heat treatment;
[0029] Figure 4 The microscopic morphology of the fracture surface of the columnar crystal yttrium oxide / magnesium oxide ceramic prepared in Example 1;
[0030] Figure 5 This is the microscopic morphology of the fracture surface of the columnar yttrium oxide / magnesium oxide ceramic prepared in Example 1 after thermal corrosion. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0032] Specific implementation method 1: The preparation method of columnar crystal yttrium oxide / magnesium oxide composite ceramic powder in this implementation method comprises the following steps:
[0033] Step 1: drying magnesium powder and a diluent; the diluent is a mixture of magnesium oxide and yttrium oxide, wherein magnesium oxide accounts for 0 to 28.19% of the total mass of the diluent;
[0034] Step 2: Evenly mix the dried magnesium powder and the diluent to obtain a mixed material; wherein the mass fraction of the magnesium powder in the mixed material is 13.45% to 24.2%, and the mass fraction of the diluent is 75.8% to 86.55%;
[0035] Step three: Load the mixed material into a high-pressure reactor, fill the high-pressure reactor with O2 or O2 mixed gas, and provide a nozzle at the lower end of the reactor, the nozzle having a nozzle diameter of 1 to 5 mm, ignite the mixed material, and perform a high-temperature combustion synthesis reaction at a reaction temperature of 3300 to 4500 K. After the reaction is completed, a high-temperature melt is formed, which is kept warm for 5 to 40 seconds, and then the nozzle is opened to spray out the high-temperature melt. After the high-temperature melt is cooled in the liquid phase, a columnar crystal yttrium oxide / magnesium oxide composite ceramic powder can be obtained; wherein the high-temperature melt spraying pressure is set to 10-40 MPa.
[0036] When the magnesium powder and the diluent are mixed evenly, a variety of mixing methods such as ball milling and stirring can be used. However, since the magnesium powder is very active, the grinding balls or stirring rods may generate heat due to friction and collision during the mixing process, causing danger. The mixing time and temperature need to be controlled during the mixing. Therefore, the present invention preferably adopts a resonance mixing method. Resonance mixing is a paddle-free mixing technology that uses vibration to conduct energy to achieve material mixing, which can avoid physical damage to the mixed materials or dangerous accidents caused by friction and collision with the grinding balls or shearing of the blades during ball milling or paddle mixing.
[0037] Specific implementation method 2: In step 1 of this implementation method, the magnesium powder is dried in a vacuum, inert gas or reducing gas. Other steps and parameters are the same as those in specific implementation method 1.
[0038] Specific implementation method 3: In step 1 of this implementation method, the drying temperature is 50-100° C. and the drying time is 12-24 hours. Other steps and parameters are the same as those in specific implementation method 1 or 2.
[0039] Specific embodiment 4: In step 1 of this embodiment, magnesium oxide accounts for 13.16% to 22.18% of the total mass of the diluent; in step 2, the mass fraction of magnesium powder in the mixed material is 16.77% to 22.77%, and the mass fraction of the diluent is 77.23% to 83.23%. Other steps and parameters are the same as those of specific embodiments 1 to 3.
[0040] The selection of the raw material range in this embodiment enables the volume ratio of Y2O3 and MgO in the obtained yttrium oxide / magnesium oxide composite ceramic powder to be 50:50. When the volume ratio of Y2O3 and MgO is 50:50, the two are each other's second phase, and the pinning effect is the strongest at this time, so that the grain size of the Y2O3-MgO composite ceramic is the smallest and the light transmission performance is the best.
[0041] Specific implementation method 5: The O2 mixed gas in step 3 of this implementation method is a mixed gas of oxygen and inert gas. The other steps and parameters are the same as those in specific implementation methods 1 to 4.
[0042] The inert gas in this embodiment is argon (Ar), which has the lowest cost.
[0043] Specific implementation method 6: In step 3 of this implementation method, the liquid phase is water or a salt solution. The other steps and parameters are the same as those of specific implementation methods 1 to 5.
[0044] The salt solution described in this embodiment is sodium chloride solution, which has the lowest cost.
[0045] Specific implementation example 7: In this implementation example, the columnar crystal yttrium oxide / magnesium oxide composite ceramic powder obtained in step 3 is sintered to obtain a submicron columnar crystal yttrium oxide / magnesium oxide composite ceramic. The other steps and parameters are the same as those in specific implementation examples 1 to 6.
[0046] Specific implementation example eight: The sintering process described in this implementation example is pressureless sintering, hot pressing sintering, spark plasma sintering or flash sintering. Other steps and parameters are the same as those of specific implementation example seven.
[0047] Specific implementation method 9: The sintering process conditions of this implementation method are: heating rate 5-100°C / min, sintering temperature 1100-1500°C, and holding time 5min-3h. Other steps and parameters are the same as those of specific implementation method 7 or 8.
[0048] Specific implementation method 10: In this implementation method, the columnar crystal yttrium oxide / magnesium oxide composite ceramic powder obtained in step 3 is firstly subjected to high-energy ball milling to 100-500 nm, and then sintered. The high-energy ball milling speed is 1000-2000 r / min, and the ball milling time is 6-12 h. The other steps and parameters are the same as those of specific implementation method 7.
[0049] In this embodiment, ball milling is performed before sintering. Ball milling can reduce the size of the powder, improve the sintering activity of the powder, reduce the sintering temperature, and reduce the grain size in the sintered ceramic.
[0050] Specific implementation eleven: In this implementation, the columnar crystal yttrium oxide / magnesium oxide composite ceramic powder obtained in step three is first sand-milled to 50-500 nm, and then sintered. The motor speed of the sand mill is 1500-2030 r / min, and the sand milling time is 4-10 hours. Other steps and parameters are the same as those of specific implementation seven.
[0051] The main function of sand milling is to reduce the powder size, improve the sintering activity, reduce the sintering temperature, and reduce the grain size in the sintered ceramic. The difference between sand milling and ball milling is that sand milling can grind the powder particle size to a smaller size.
[0052] The embodiments of the present invention are described in detail below. The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation schemes and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.
[0053] Embodiment 1:
[0054] The preparation method of the columnar crystal Y2O3 / 50vol%MgO composite ceramic powder in this embodiment is specifically completed by the following steps:
[0055] 1. Drying magnesium powder, yttrium oxide powder and magnesium oxide powder. Magnesium powder is dried under vacuum degree of 0.06MPa, drying temperature is 80℃, and drying time is 12h. Yttrium oxide powder and magnesium oxide powder are directly dried at drying temperature of 80℃ and drying time is 12h.
[0056] 2. Mix 30.5 g of dried magnesium powder, 27.5 g of magnesium oxide powder and 109.4 g of yttrium oxide powder by resonance mixing method, and pass through a 60-mesh sieve to obtain a mixed material;
[0057] 3. The mixed material is loaded into a high-pressure reactor and filled with O2. The oxygen pressure is set to 19.1MPa. A nozzle is provided at the lower end of the high-pressure reactor. The nozzle orifice size is Φ2mm. The high-pressure reactor is placed above a water cooling device. The resistance wire ignites the mixed material to perform a high-temperature combustion synthesis reaction. After the reaction is completed, a high-temperature melt is formed. The temperature is kept for 7s, and then the nozzle is opened. The high-temperature melt is ejected through the nozzle under high temperature and high pressure and sprayed into the water cooling device for liquid phase cooling to obtain yttrium oxide / magnesium oxide composite ceramic powder; the water cooling device is an atomizing tower filled with a cooling liquid phase, and the cooling liquid phase is water;
[0058] 4. The powder obtained in step 3 is subjected to spark plasma sintering to obtain columnar crystal yttrium oxide / magnesium oxide composite ceramics. The spark plasma sintering conditions are: sintering temperature 1200° C., sintering pressure 50 MPa, heating rate 100° C. / min, and heat preservation for 10 min.
[0059] 5. Anneal the yttrium oxide / magnesium oxide composite ceramic obtained in step 4 in air, and the annealing conditions are: annealing temperature 1000° C., and annealing time 10 h.
[0060] The fracture toughness of the ceramic prepared in this embodiment was tested by indentation method. The performance before annealing was: fracture toughness 2.6 MPa·m 1 / 2 , hardness 12.9GPa; after annealing, the properties are: fracture toughness 3.4MPa·m 1 / 2 , hardness 11.0GPa.
[0061] The phase composition and microstructure of the yttrium oxide / magnesium oxide composite ceramic powder obtained in Example 1 were analyzed. Figure 1 The XRD patterns of the columnar crystalline yttrium oxide / magnesium oxide composite ceramic powder prepared in Example 1 after heat treatment at different temperatures, ■ represents m-Y2O3, ● represents c-Y2O3, ◆ represents MgO, and the phase composition of the powder before heat treatment is m-Y2O3, cubic phase MgO and a small amount of c-Y2O3. After heat treatment, the m-Y2O3 in the powder gradually transforms into c-Y2O3, and is completely transformed into c-Y2O3 at 1000°C, and the final phase composition of the powder is c-Y2O3 and cubic phase MgO. Figure 2is the cross section and EDS analysis of the composite ceramic powder obtained in step 3 of Example 1, Figure 2 The atomic percentages of the three elements O, Mg and Y at different positions in the graph are shown in Table 1. Point 1 and Point 2 correspond to Figure 2 Point 1 and Point 2 in the left figure, Plane Scan is the atomic percentage of the three elements O, Mg and Y in the entire cross-section. When the volume ratio of Y2O3 and MgO is 50:50, the atomic ratio of Y and Mg is 1:2. The result of PlaneScan shows that the atomic ratio of Y and Mg is close to 1:2, indicating that the volume ratio of Y2O3 and MgO in the synthesized powder is 50:50. Point 1, that is, the atomic ratio of Y and Mg in the light-colored phase is greater than 1:2, while Point 2, that is, the atomic ratio of Y and Mg in the dark-colored phase is less than 1:2. This result shows that Y2O3 and MgO are mutually soluble at high temperatures and retain this solid solution state in the powder obtained by rapid cooling. At the same time, Figure 2 It can be seen that there are dendrites in the composite ceramic powder, and the dendrites are solid solutions of yttrium oxide and magnesium oxide.
[0062] Figure 3 The surface microstructure of the prepared yttrium oxide / magnesium oxide composite ceramic powder after heat treatment. Figure 3 It can be seen that there are high-density columnar crystals on the surface of the composite ceramic, and the radial size of the columnar crystals is about 30-100nm. Figure 4 The fracture morphology of spark plasma sintered yttria / magnesium oxide composite ceramics before and after annealing. The left picture is before annealing, and the right picture is after annealing. Pulled-out columnar crystals (yellow arrows) and pulled-out holes (green arrows) can be observed on the fracture surface before and after annealing. During the sintering process, the metastable supersaturated solid solution decomposes and precipitates to form a small amount of columnar crystals. The high heating and cooling rates and the short holding time make the microstructure of the ceramics after sintering not reach a completely stable state, and a high solid solubility remains. During the annealing process, the columnar crystals further precipitate and grow, so that more columnar crystal structures that play a toughening role during fracture can be observed on the fracture surface of the annealed ceramics.
[0063] In order to observe the microstructure of the prepared yttrium oxide / magnesium oxide composite ceramic more clearly, the sample was hot-etched at 1000℃ for 2h. The microstructure of the fracture surface after hot-etching is shown in Figure 2. Figure 5 As shown, the right picture is the enlarged picture of the red box on the left picture. Figure 5 It can be seen that the interior of the ceramic is composed of submicron Y2O3 and MgO, the grain size is between 500-800nm, and high-density columnar crystals are observed both between and within the crystals.
[0064] Table 1
[0065] Location O / at% Mg / at% Y / at% Point 1 61.93 23.91 14.16 Point2 52.26 33.75 13.99 Plane Scan 53.98 29.74 16.28
[0066] Embodiment 2:
[0067] The preparation method of the columnar crystal Y2O3 / 50vol%MgO composite ceramic powder in this embodiment is specifically completed by the following steps:
[0068] 1. Drying magnesium powder, yttrium oxide powder and magnesium oxide powder. Magnesium powder is dried under vacuum degree of 0.06MPa, drying temperature is 80℃, and drying time is 12h. Yttrium oxide powder and magnesium oxide powder are directly dried at drying temperature of 80℃ and drying time is 12h.
[0069] 2. Mix 32.6 g of dried magnesium powder, 23.8 g of magnesium oxide powder and 108.8 g of yttrium oxide powder by resonance mixing method, and pass through a 60-mesh sieve to obtain a mixed material;
[0070] 3. Load the mixed material into a high-pressure reactor, fill it with O2, and set the oxygen pressure to 20.34MPa. A nozzle is provided at the lower end of the high-pressure reactor, and the nozzle size of the nozzle is Φ2mm. Place the high-pressure reactor above a water cooling device, ignite the mixed material with a resistance wire, and perform a high-temperature combustion synthesis reaction. After the reaction is completed, a high-temperature melt is formed. The heat is kept for 10s, and then the nozzle is opened. The high-temperature melt is ejected through the nozzle under high temperature and high pressure, and sprayed into the water cooling device for liquid phase cooling to obtain yttrium oxide / magnesium oxide composite ceramic powder; the water cooling device is an atomizing tower filled with a cooling liquid phase, and the cooling liquid phase is water.
[0071] 4. The powder obtained in step 3 is subjected to hot pressing and sintering to obtain columnar crystal yttrium oxide / magnesium oxide composite ceramics. The hot pressing and sintering conditions are: sintering temperature 1300° C., sintering pressure 40 MPa, heating rate 20° C. / min, and heat preservation for 1 hour;
[0072] 5. Anneal the yttrium oxide / magnesium oxide composite ceramic obtained in step 4 in air, and the annealing conditions are: annealing temperature 1000° C., and annealing time 10 h.
[0073] The fracture toughness of the ceramic prepared in this embodiment was tested by indentation method. The performance before annealing was: fracture toughness 3.2 MPa·m 1 / 2 , hardness 12.5GPa; after annealing, the performance is: fracture toughness 3.7MPa·m 1 / 2 , hardness 11.2GPa.
[0074] Embodiment 3:
[0075] The preparation method of the columnar crystal Y2O3 / 40vol%MgO composite ceramic powder in this embodiment is specifically completed according to the following steps:
[0076] 1. Drying magnesium powder, yttrium oxide powder and magnesium oxide powder. Magnesium powder is dried under vacuum degree of 0.06MPa, drying temperature is 80℃, and drying time is 12h. Yttrium oxide powder and magnesium oxide powder are directly dried at drying temperature of 80℃ and drying time is 12h.
[0077] 2. Mix 30.7 g of dried magnesium powder, 11.7 g of magnesium oxide powder and 131.3 g of yttrium oxide powder by resonance mixing method, and pass through a 60-mesh sieve to obtain a mixed material;
[0078] 3. The mixed material is loaded into a high-pressure reactor and filled with O2. The oxygen pressure is set to 19.15MPa. A nozzle is provided at the lower end of the high-pressure reactor. The nozzle orifice size is Φ2mm. The high-pressure reactor is placed above a water cooling device. The resistance wire ignites the mixed material to perform a high-temperature combustion synthesis reaction. After the reaction is completed, a high-temperature melt is formed. The heat is kept for 7s, and then the nozzle is opened. The high-temperature melt is ejected through the nozzle under high temperature and high pressure and sprayed into the water cooling device for liquid phase cooling to obtain yttrium oxide / magnesium oxide composite ceramic powder; the water cooling device is an atomizing tower containing a cooling liquid phase, and the cooling liquid phase is water.
[0079] 4. The powder obtained in step 3 is subjected to spark plasma sintering to obtain columnar crystalline yttrium oxide / magnesium oxide composite ceramics. The spark plasma sintering conditions are: sintering temperature 1100° C., sintering pressure 50 MPa, heating rate 100° C. / min, and heat preservation for 5 min.
[0080] 5. Anneal the yttrium oxide / magnesium oxide composite ceramic obtained in step 4 in air, and the annealing conditions are: annealing temperature 1000° C., annealing time 24 h.
[0081] The fracture toughness of the ceramic prepared in this embodiment was tested by indentation method. The performance before annealing was: fracture toughness 2.9 MPa·m 1 / 2 , hardness 13.0GPa; after annealing, the performance is: fracture toughness 3.3MPa·m 1 / 2 , hardness 12.1GPa.
[0082] Embodiment 4:
[0083] The preparation method of the columnar crystal Y2O3 / 30vol%MgO composite ceramic powder in this embodiment is specifically completed by the following steps:
[0084] 1. Dry the magnesium powder and yttrium oxide powder. The magnesium powder is vacuum dried at a vacuum degree of 0.06 MPa, the drying temperature is 80°C, and the drying time is 12 hours. The yttrium oxide powder and magnesium oxide powder are directly dried at a drying temperature of 80°C and the drying time is 12 hours.
[0085] 2. Mix 28.4 g of dried magnesium powder and 154.2 g of yttrium oxide powder by resonance mixing method, and pass through a 60-mesh sieve to obtain a mixed material;
[0086] 3. Load the mixed material into a high-pressure reactor and fill it with O2. The oxygen pressure is set to 17.8MPa. A nozzle is provided at the lower end of the high-pressure reactor. The nozzle orifice size is Φ2mm. The high-pressure reactor is placed above a water cooling device. The resistance wire ignites the mixed material to perform a high-temperature combustion synthesis reaction. After the reaction is completed, a high-temperature melt is formed. The temperature is kept for 7s, and then the nozzle is opened. The high-temperature melt is ejected through the nozzle under high temperature and high pressure and sprayed into the water cooling device for liquid phase cooling to obtain yttrium oxide / magnesium oxide composite ceramic powder; the water cooling device is an atomizing tower containing a cooling liquid phase, and the cooling liquid phase is water.
[0087] 4. The powder obtained in step 3 is subjected to hot pressing and sintering to obtain columnar crystal yttrium oxide / magnesium oxide composite ceramics. The hot pressing and sintering conditions are: sintering temperature 1200° C., sintering pressure 30 MPa, heating rate 20° C. / min, and heat preservation for 1 hour;
[0088] 5. Anneal the yttrium oxide / magnesium oxide composite ceramic obtained in step 4 in air, and the annealing conditions are: annealing temperature 1000° C., and annealing time 10 h.
[0089] The fracture toughness of the ceramic prepared in this embodiment was tested by indentation method. The performance before annealing was: fracture toughness 3.0 MPa·m 1 / 2 , hardness 11.8GPa; after annealing, the performance is: fracture toughness 3.5MPa·m 1 / 2 , hardness 11.2GPa.
Claims
1. A method for preparing columnar crystal yttrium oxide / magnesium oxide composite ceramic powder, characterized in that: The method comprises the following steps: Step 1: drying magnesium powder and a diluent; the diluent is a mixture of magnesium oxide and yttrium oxide, wherein magnesium oxide accounts for 0 to 28.19% of the total mass of the diluent; Step 2: Evenly mix the dried magnesium powder and the diluent to obtain a mixed material; wherein the mass fraction of the magnesium powder in the mixed material is 13.45% to 24.2%, and the mass fraction of the diluent is 75.8% to 86.55%; Step three: Load the mixed material into a high-pressure reactor, fill the high-pressure reactor with O2 or O2 mixed gas, and provide a nozzle at the lower end of the reactor, the nozzle having a nozzle diameter of 1 to 5 mm, ignite the mixed material, and perform a high-temperature combustion synthesis reaction at a reaction temperature of 3300 to 4500 K. After the reaction is completed, a high-temperature melt is formed, which is kept warm for 5 to 40 seconds, and then the nozzle is opened to spray out the high-temperature melt. After the high-temperature melt is cooled in the liquid phase, a columnar crystal yttrium oxide / magnesium oxide composite ceramic powder can be obtained; wherein the high-temperature melt spraying pressure is set to 10 to 40 MPa.
2. The method for preparing a columnar crystal yttrium oxide / magnesium oxide composite ceramic powder according to claim 1, characterized in that: The magnesium powder in step 1 is dried in vacuum, inert or reducing gas.
3. The method for preparing a columnar crystal yttrium oxide / magnesium oxide composite ceramic powder according to claim 1 or 2, characterized in that: In step 1, the drying temperature is 50-100° C. and the drying time is 12-24 hours.
4. The method for preparing a columnar crystal yttrium oxide / magnesium oxide composite ceramic powder according to claim 1, characterized in that: In step 1, magnesium oxide accounts for 13.16% to 22.18% of the total mass of the diluent; in step 2, the mass fraction of magnesium powder in the mixed material is 16.77% to 22.77%, and the mass fraction of the diluent is 77.23% to 83.23%.
5. The method for preparing a columnar crystal yttrium oxide / magnesium oxide composite ceramic powder according to claim 1, characterized in that: The O2 mixed gas in step 3 is a mixed gas of oxygen and inert gas.
6. The method for preparing a columnar crystal yttrium oxide / magnesium oxide composite ceramic powder according to claim 1, characterized in that: The columnar crystal yttrium oxide / magnesium oxide composite ceramic powder obtained in step three is sintered to obtain submicron columnar crystal yttrium oxide / magnesium oxide composite ceramic.
7. The method for preparing a columnar crystal yttrium oxide / magnesium oxide composite ceramic powder according to claim 6, characterized in that: The sintering process is pressureless sintering, hot pressing sintering, spark plasma sintering or flash sintering.
8. The method for preparing a columnar crystal yttrium oxide / magnesium oxide composite ceramic powder according to claim 6 or 7, characterized in that: The conditions of the sintering process are: heating rate of 5 to 100° C. / min, sintering temperature of 1100 to 1500° C., and holding time of 5 min to 3 h.
9. The method for preparing a columnar crystal yttrium oxide / magnesium oxide composite ceramic powder according to claim 6, characterized in that: First, the columnar crystal yttrium oxide / magnesium oxide composite ceramic powder obtained in step three is subjected to high-energy ball milling to 100-500 nm, and then sintered; the high-energy ball milling speed is 1000-2000 r / min, and the ball milling time is 6-12 h.
10. The method for preparing a columnar crystal yttrium oxide / magnesium oxide composite ceramic powder according to claim 6, characterized in that: First, the columnar crystal yttrium oxide / magnesium oxide composite ceramic powder obtained in step three is sand-milled to 50-500 nm, and then sintered; the motor speed of the sand mill is 1500-2030 r / min, and the sand-milling time is 4-10 hours.
Citation Information
Patent Citations
Method for preparing high performance yttrium oxide material
CN101462760A
Method for preparing superfine boron carbide powder
CN101570438A
Method of synthesizing MgO / Y2O3 nano powder by microwave combustion
CN103951392A
Method for preparing mixture of alumina-based amorphous and solid solution ceramic micron powder by using aluminum oxygen combustion synthesis quenching method
CN108751956A
Method for preparing mixture of alumina based amorphous and solid solution ceramic micron powder by high temperature melt quenching method
CN108821782A